Laser-clad Nb(Ta)TiZr medium-entropy alloy coatings on pure Zr sheet: Microstructural characteristics, hardness and wear resistance. (April 2022) - Guan, Haotian; Chai, Linjiang; Wu, Juying; Gong, Xingyu; Xiang, Kang; Wu, Lu; Pan, Hucheng; Li, Yuqiong; Wang, Qiusen
Abstract: In this work, two Nb(Ta)TiZr medium-entropy alloy (MEA) coatings were fabricated successfully on a commercially pure Zr sheet by pulsed laser cladding. Their phase constitutions, microstructural characteristics, chemical compositions and grain orientations were well characterized and analyzed by using X-ray diffraction (XRD), electron channeling contrast (ECC) imaging, energy dispersive spectrometry (EDS) and electron backscatter diffraction (EBSD) techniques, with hardness and wear resistance measured and correlated with the microstructural characteristics as well. Results show that irregular-shaped bulk grains (BCC solid-solution phase) are formed in the two Nb(Ta)TiZr MEA coatings (cladding zones), both of which have a thickness of ∼800 μm with good metallurgical bonding to the substrate. After adding Ta, grains in the MEA coating are slightly refined. The phase constitutions in both the coatings agree with calculations based on several theoretical parameters. Hardness tests show that the NbTiZr and the NbTaTiZr coatings have hardnesses of 360 ± 18 HV and 430 ± 28 HV, respectively, ∼1.8 times and ∼2.2 times that of the substrate (196 ± 4 HV). This can be ascribed to combined effects of grain refinement strengthening, solid solution strengthening with denser low angle boundaries in the MEA coatings. Specific wear rates of the NbTiZr and the NbTaTiZr coatings are only ∼17% and ∼6% of that of the substrate, respectively, indicating markedly improved wear resistance. This is demonstrated to be closely related to complete oxide films easily formed on the coatings with oxidation and abrasive wear mechanisms. Highlights: Two Nb(Ta)TiZr MEA coatings were prepared on a pure Zr sheet by pulsed laser cladding. The MEA coatings have a thickness of ∼800 μm and consist of irregular-shaped BCC phase. Hardness and wear resistance of both MEA coatings are greatly improved compared to the substrate. Their superior properties are related to grain refinement, solid solution and denser low angle boundaries.